The Effect of Proposed Strategy According to the Realistic Mathematics Theory on the Achievement and Mathematical Interrelation of third Intermediate Students (Journal Of Educational and Psychological Researches, 2023)
AbstractThe current research aims to identify the effect of the proposed strategy in accordance with realistic mathematics on the achievement and mathematical Interrelation of third Intermediate students. Two samples were tested from the middle third grade in a school affiliated with the General Directorate of Baghdad- Rusafa, the first for the academic year (2022-2021). The experimental group is (30) students taught according to the proposed strategy, and the control group is (30) students based on the traditional method. To achieve the research objective, the researchers developed a test for achievement consisting of (30) items and a test of sports interconnection composed of (20) items. The results of the study showed that there are statistically significant differences between the mean scores of the students of the two groups in the achievement test and the mathematical correlation test in favor of the experimental group.